Applying Augmented Reality-Based Fun Book Technology (Round Table Learning Media) for Teaching-Learning of Coastal Community - Muhammad Bayu Purnama; Zayus Rifan Zafarani; Sapta Nugraha (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2020)
Malang Rapat is one of the villages which is located in the range of coastal region, Bintan regency, Riau islands Province. Most people in this village do not complete elementary level of education. Only a few graduate from Elementary School, Junior High School and Senior High School. The rate of education and its quality of human resources are very low. This condition is due to the monotonous system of teaching-learning process and lack of facilities and infrastructures. These are the problems that cause low quality of education. This research aims at developing teaching-learning process by applying Augmented Reality-Based Fun Book Technology (Round Table Learning Media) for Teaching-Learning of Coastal Community. This application is to develop knowledge by applying quizzes and games. The result obtained is that this technology is capable for handling the problems of low quality of education with its monotonous system of teaching-learning process.